KEMANDIRIAN BELAJAR PETANI DALAM MENINGKATKAN KOMPETENSI DI ERA TEKNOLOGI KOMUNIKASI DAN INFORMASI - Yuni Sugiarti; Arif Imam Suroso; Irman Hermadi; Euis Sunarti (Kwangsan: Jurnal Teknologi Pendidikan, 2023)
In the era of Information and Communication Technology, the competency of Aglaonema farmers needs to have learning independence in line with the demands of the times. The purpose of this study is to find out the constraints of aglaonema farmers in increasing competence in aspects of production and marketing quality, and to examine the solution through the implementation of a Knowledge Management System. The method used in this research is qualitative method. The technique of collecting data through in-depth interviews and literature review. The results of the data analysis show that the constraints of Aglaonema farmers are that there is very little communication and cooperation, lack of innovation, conventional marketing, very little use of ICT, lack of support from research and development institutions from the government/relevant agencies, and less effective farmer groups. Efforts to increase farmer competence can implement a Knowledge Management System, so that farmers can learn from various sources, share experiences and communicate with stakeholders from upstream to downstream.AbstrakPada era Teknologi Informasi dan Komunikasi, kompetensi petani Aglaonema perlu memiliki kemandirian belajar seiring tuntutan perkembangan zaman. Tujuan dari penelitian ini untuk mengetahui kendala-kendala petani aglaonema dalam meningkatkan kompetensi pada aspek kualitas produksi dan pemasaran, serta mengkaji solusinya melalui implementasi Knowledge Management System. Metode yang digunakan dalam penelitian ini adalah metode kualitatif. Teknik pengumpulan data melalui wawancara mendalam dan kajian literatur. Hasil analisis data diketahui kendala-kendala petani Aglaonema adalah komunikasi dan kerjasama sangat kurang, kurang berinovasi, pemasaran konvensional, penggunaan TIK sangat kurang, dukungan lembaga riset dan pembinaan dari pemerintah/dinas terkait masih kurang, serta kelompok petani kurang efektif. Upaya meningkatkan kompetensi petani tersebut dapat mengimplementasikan Knowledge Management System, sehingga petani dapat belajar dengan berbagai sumber, sharing pengalaman dan komunikasi dengan para pemangku kepentingan dari hulu ke hilir.